2007
DOI: 10.1002/pssc.200673872
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of transition metal ion‐doped MgAl2O4 spinel for laser application

Abstract: Ti and Mn-doped MgAl 2 O 4 spinel have been successfully grown by the micro-pulling-down method and spectroscopic properties have been investigated in view of the potential use as a short-wavelength tunable solid-state laser. Strong blue emission is observed from Ti-doped MgAl 2 O 4 and green emission from a Mn-doped one. The optimum conditions to obtain the strongest emission were studied by changing the doping concentration. These two broad emission bands around 455 nm for Ti (decay time of 5.7 µs) and 518 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 13 publications
0
35
0
2
Order By: Relevance
“…As we have seen in XRD patterns, two new phases Al 2 O 3 and MgAl 2 O 4 appear as the ratio of Mg/Ca increases. Based on the previous studies, no evidence of Mn 4+ ions in the MgAl 2 O 4 phase was observed [15,16]. It suggests that the emission peak at 14,750 cm −1 is attributed to the 2 E-4 A 2 transition of Mn 4+ ions in Al 2 O 3 .…”
Section: Resultsmentioning
confidence: 92%
“…As we have seen in XRD patterns, two new phases Al 2 O 3 and MgAl 2 O 4 appear as the ratio of Mg/Ca increases. Based on the previous studies, no evidence of Mn 4+ ions in the MgAl 2 O 4 phase was observed [15,16]. It suggests that the emission peak at 14,750 cm −1 is attributed to the 2 E-4 A 2 transition of Mn 4+ ions in Al 2 O 3 .…”
Section: Resultsmentioning
confidence: 92%
“…As we have seen in the XRD patterns, two new phases of Al 2 O 3 and MgAl 2 O 4 grow up as the ratio of Mg/Ca increases. Based on the previous studies, no evidence of Mn 4 + ions in the MgAl 2 O 4 phase was observed [14,15], which suggests that the emission peak at 678 nm is due to the 2 E-4 A 2 transition of Mn 4 + in Al 2 O 3 . The vibronic bands of Mn 4 + in the Al 2 O 3 spread to 720 nm and overlap a part of the vibronic transitions of Mn 4 + in the CAO phase, which also contribute to the integrated intensity of the red luminescence band.…”
Section: Resultsmentioning
confidence: 94%
“…Recently, intensive investigations have been carried out on the utilization of MgAl 2 O 4 as a matrix for various phosphors. These investigations are useful because spinel is a promising candidate for divalent and trivalent phosphors (Cr 3+ , Co 2+ , Mn 2+ , Ni 2+ , Tb 3+ ) owing to a large number of empty tetrahedral and octahedral sites in its crystal structure …”
Section: Introductionmentioning
confidence: 99%